Utilization of Microsoft Excel-Based Applications for Ease of Acceptance Management of PKL or Intern Student Activities at Ngimbang Lamongan Hospital - Sujono -; Eky Mita Nisayanti; Muhyiddin Zainul Arifin (KH. A. Wahab Hasbullah University, 2023)
Along with the development of technology and the improvement of socio-economic life in the community, the community's expectations for improving health services and the expectations of patients for health workers have also increased. An agency or institution needs a system or media that can help their needs in achieving work efficiency and effectiveness to improve the quality of service to the community. In this case, the COMMORDIC of the Ngimbang Regional General Hospital has not yet integrated its information system, so there are often difficulties in managing student admissions for internships. So an application or media is needed to facilitate KOMKORDIK in mapping and integrating information systems at Ngimbang Hospital. One of the data processing applications that can be operated freely or without payment and is easy to use is the Microsoft Excel application. Microsoft Excel is designed with functions to help solve administrative problems starting from the simplest to the more complex parts. In making this information system using the waterfall method because the system created is not too large and the scope of development is not so wide that it will be easier if you use the waterfall model, the approach is carried out systematically and sequentially. Making this Microsoft Excel-based information system can assist in processing student data such as student origin data, activity schedule data, and room data that has been provided. The existence of this information system can also help carry out data processing of PKL / Internship student activities effectively and efficiently